1999
DOI: 10.1021/ma9814651
|View full text |Cite
|
Sign up to set email alerts
|

MALDI-TOF Characterization of Highly Cross-Linked, Degradable Polymer Networks

Abstract: Multifunctional anhydride monomers were synthesized and photopolymerized to form highly cross-linked, degradable networks. The networks were synthesized from monomers and oligomers of dimethacrylated sebacic acid of varying molecular weight, as well as under varying reaction conditions. The cross-linked polymers were subsequently degraded in phosphate buffered saline, and the degradation products, sebacic acid and poly(methacrylic acid), were isolated. Matrix-assisted laser desorption/ionization time-of-flight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
39
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 27 publications
3
39
0
Order By: Relevance
“…In contrast, few MS studies have been reported for PMAA and most of them focused on the analysis of volatile thermal degradation products of the polymer [33,34]. Intact PMAA oligomer ions could be produced by matrix assisted laser desorption/ionization (MALDI) [35][36][37][38]. Although mass averages from these MS data were often biased to low molecular weight and produced with poor signal-to-noise ratios, information regarding absolute masses of each individual macromolecular species was available, allowing monomer and end-group masses to be confirmed.…”
mentioning
confidence: 99%
“…In contrast, few MS studies have been reported for PMAA and most of them focused on the analysis of volatile thermal degradation products of the polymer [33,34]. Intact PMAA oligomer ions could be produced by matrix assisted laser desorption/ionization (MALDI) [35][36][37][38]. Although mass averages from these MS data were often biased to low molecular weight and produced with poor signal-to-noise ratios, information regarding absolute masses of each individual macromolecular species was available, allowing monomer and end-group masses to be confirmed.…”
mentioning
confidence: 99%
“…The analytical protocols used in positive ion mode are 2,5-dihydroxybenzoic acid (DHB) matrix in methanol [4] or DHB and sodium trifluoroacetate in acetone [5]. Sinapinic acid in methanol (MeOH) or water (H 2 O) has been used in negative ion mode [6]. Consistent throughout these data are very poor signal-to-noise ratios and non-isotopic resolution of the observed species.…”
mentioning
confidence: 99%
“…Anseth et al investigated the volume shrinkage, conversion, and kinetic chain length in the cross-linked network structure by means of kinetic measurement, matrix assisted laser desoprption/ionization time-of-flight mass spectroscopy (MALDI-TOF MS), and gel permeation chromatography [2][3][4]. Their results indicated the existence of diffusioncontrolled kinetics which is affected by the cross-linked network.…”
Section: Introductionmentioning
confidence: 99%